IDENTIFIKASI MINYAK CITRONELLA DENGAN GCMS DAN APLIKASINYA SEBAGAI MINYAK ANGIN AROMATERAPI [Identification of Citronella Oil With GCMS and Its Application In Aromatherapy Medicated Oil Formulation] - Shintawati Shintawati; Zulfahmi Zulfahmi (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2020)
This study aimed to identify citronella oil and find its application as safe aromatherapy medicated oil preferred by consumers. Medicated oil was made in 4 formulas with the ratio of menthol crystals, white oil, gandapura oil, citronella oil, peppermint oil and lemon oil 6: 1: 5: 2: 2: 4; 6: 1: 5: 0: 2: 6; 6: 1: 5: 0: 8: 0 and 6: 1: 5: 8: 0: 0. GCMS results showed that there were 60 volatile organic compounds in citronella oil with alcohol as the most abundant component and contained several compounds that play a role in the development of aromatherapy wind oil products, namely cyclopropane, geraniol, and nerol. The four aromatherapy formulas with a pH of 4.96-5.37, were safe for the skin, non-irritating, stable, and complied with BPOM Head Regulation No. 12 of 2014 with total microbial content of 0-4.5 x 103 colonies/ml. Based on color, natural fragrance, freshness, the warmth, texture and over all likeness, formula with menthol crystal, white oil, gandapura oil, citronella oil, peppermint oil and lemon oil with ratio of 6: 1: 5: 2: 2: 4 and 6: 1: 5: 8: 0: 0 have the highest value of the preference.Keywords: GCMS, aromatherapy and citronella oil